An experimental investigation of flow pattern around vertical pile due to a turbulent jet - Yuksel, Ayse; Celikoglu, Yesim; Yuksel, Yalcin (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 2006)
The scouring around piles in the harbors caused by ship propellers is an increasing problem. Prediction of flow patterns around the piles has an important role in protection and design of the quay piles. The protection of the pile basin against to scour is too expensive. Because of this, the determination of the flow characteristics around piles is very important. This work is a preliminary study of the searching the flow characteristics around piles experimentally. Propeller jet was analogized to a circular turbulent jet. The objective of this study is to investigate the flow mechanism of the 3D circular turbulent water jet around a cylindrical pile.
Keywords: 3D Jet; free jet; wall jet; pile; ADV; FIELD; Engineering